PLS3 predicts poor prognosis in pancreatic cancer and promotes cancer cell proliferation via PI3K/AKT signaling. Issue 11 (2nd April 2020) - Xin, Zechang; Li, Duguang; Mao, Feiyu; Du, Yan; Wang, Xiaodong; Xu, Peng; Li, Zhennan; Qian, Jianjun; Yao, Jie
Abstract: Plastin‐3 plays a key role in cancer cell proliferation and invasion, but its prognostic value in pancreatic cancer (PACA) remains poorly defined. In this study, we show that PLS3 messenger RNA is overexpressed in PACA tissue compared with normal tissue. We accumulated 207 cases of PACA specimens to perform immunohistochemical analysis and demonstrated that PLS3 levels correlate with T‐classification ( p < .001) and pathology ( p < .001). Furthermore, overall survival rates ( p < .001) in tumors with high PLS3 expression were poor, as assessed through Kaplan–Meier survival analysis. PLS3 was found to be an independent prognostic factor for PACA through multivariate Cox regression analysis. Moreover, we found that PLS3 enhances the proliferation and invasion of tumor cells as assessed through Cell Counting Kit‐8, wounding healing assays, and Transwell assays. The upregulation of PLS3 also led to enhanced phosphatidylinositol‐3 kinase/protein kinase B signaling in PACA cells. These data suggest that PLS3 is a biomarker to estimate PACA progression and represents a molecular target for PACA therapy. Abstract : In our study, we found that PLS3 is overexpressed in pancreatic cancer (PACA) cells and tissues and can be a predictor for the overall survival of patients with PACA. PLS3 promoted the proliferative and invasive capacity of PACA cells. PLS3 through phosphatidylinositol‐3 kinase/protein kinase B signaling to regulate PACA progression.